Urgensi Pembuatan Perjanjian Penerbitan Surat Utang Berjangka (Medium Term Notes) oleh Notaris - Vianny, Maena; Prasanthi Sigit, Antarin (Universitas Ekasakti, 2023)
The Financial Services Authority (OJK) issued Financial Services Authority Regulation (POJK) No.30/POJK.04/2019 concerning the Issuance of Debt Securities and/or Sukuk Conducted Without a Public Offering (from now on referred to as POJK EBUS) as a legal umbrella for issuance agreements Term Debt Securities or Medium Term Notes (from now on referred to as MTN). However, in reality, defaults on payments to MTN still occur frequently at this time. Moreover, in POJK EBUS there are no provisions explaining the making of an MTN Issuance Agreement by a capital market notary whereas in Circular Letter No. SE-0005/DIR-EKS/KSEI/1121 concerning the Mechanism for Registration of Debt Securities and/or Sukuk at PT Kustodian Sentral Efek Indonesia (KSEI) (hereinafter referred to as SE KSEI concerning EBUS Registration) explains the obligation to make the agreement by a capital market notary which has been registered with the OJK. The purpose of this research is to analyze the provisions in force in Indonesia regarding MTN Issuance Agreements, and the authority of notaries in making MTN Issuance Agreements. This doctrinal research collects secondary data through literature study, which is then analyzed qualitatively. From the results of the analysis, it can be explained that there are several factors that led to MTN's default, namely the Covid-19 pandemic, the bankruptcy of the securities issuing company and manipulation of the financial reports of the securities issuing company. The MTN Issuance Agreement itself should be made in the form of an authentic deed before a notary to guarantee legal certainty and protection for the parties because the authentic deed is a perfect means of proof if a dispute arises in the future.